Incomplete Diversification and Asset Pricing - Dilip B. Madan; Frank Milne; Robert Elliott (Queen's University, Department of Economics, 1992)
Investors in equilibrium are modeled as facing investor specific risk exposures arising from incomplete diversification of personal risks across the space of assets. Personalized asset pricing models reflect these risks. Averaging across the pool of investors we obtain a market asset pricing model that reflects market risk exposures. It is observed on invoking a law of large number applied to an infinite population of investors that many personally relevant risk considerations can be eliminated from the market asset pricing model. Examples illustrating the effects of undiversified labour income and taste specific price indices are provided. Suggestions for future work on asset pricing include a need to focus on identifying and explaining investor specific risk exposures.
Keywords: 330